Long Term Rigid Retained Foreign Object After Breast Augmentation: A Case Report and Literature Review - Franco, Coral; Moskovitz, Anner; Weinstein, Iuliana; Kwartin, Samuel; Wolf, Yoram (Frontiers in Surgery, 2021)
Introduction: Retained foreign object (RFO) is a rare iatrogenic complication. This article presents an unprecedented case of a plastic RFO post augmentation mammoplasty. Case presentation: We present the case of a 32-year-old woman, eight years after breast augmentation surgery, with a four year history of a palpable migrating mass in the superior lateral quadrant of her right breast with fluctuating levels of pain. Imaging studies included mammography tests, sonographic examinations, a Magnetic Resonance Imaging scan, and a Computed Tomography scan, all of which did not identify any pathological findings. Exploratory surgery discovered a syringe-tip cover in the implant pocket. Conclusion: Persistent complaints and symptoms accompanied by nonspecific imaging studies warrant escalation of diagnostic methods, in line with a high awareness for the possibility of an RFO. As pocket lavage is a common practice in various surgeries, this report can serve as a valuable reminder for surgical teams to account for syringe covers and other disposable items at the end of all operations.